Attitudes towards HIV/AIDS: the voices of Zimbabwean high school students - Gudyanga, Ephias; Mashini, Alfred; Gudyanga, Anna (2016)
This study sought to find out attitudes of high school students towards HIV/AIDS. A random sample of 80 students, from two conveniently selected schools (40 males, 40 females; age range, 12-19 years) from form one to six, participated in the study. Attitude measures were obtained using Likert type scale. Majority (92%) of the high school students were found to be knowledgeable about HIV/AIDS, however, during the 12 months preceding the survey, 10% of the sample abstained from sexual intercourse, 10 % indicated that they engaged in heterosexuality well before age 14, about 20% never used condoms whenever they had sex, about 40% get involved in age-mixing sexual relationships, 25% of the sample had been tested for HIV. It was recommended that the education and the health sectors among others should increase HIV/AIDS education to the high school students.